PELATIHAN PENCEGAHAN PENYAKIT KULIT AKIBAT JAMUR PADA SISWA SMP NEGERI 2 MANADO - Pinontoan, S.P.M.; Sunati, N.; Rasyid, R.A.; Lalangpuling, I.E. (Buletin Udayana Mengabdi; Vol 23 No 1 (2024): Buletin Udayana Mengabdi, 2023)
Skin disease is one of the health problems in Indonesia, some of them are caused by fungi. Hormonal changes or increased sebum secretion in the body and high activity during adolescence, can be a risk factor for fungal diseases of the skin. The purpose of this dedication is to train students on the prevention of fungal skin diseases and to identify fungi that cause skin diseases. The methods used in the training are lectures, demonstration, practice and discussion while the method used for the eximination of fungi using the direct examination method. Evaluation of training programme using pre-test and post-test techniques. The average pre-test score was 47.42 and the post-test average was 79.03, indicating an increase in knowledge after being given trainin. Practise result show that some of students skin have characteristics such as white patches, some are brown, itchy, found on the neck, face and back. Another feature is a ring-shaped rash, with slightly raised edges and scaly skin. The results of the examination using skin scraping samples from 26 respondents with 10% KOH solution, obtained positive results from 12 (46.15%) samples and negative results from 14 (53.85%) samples. Keywords: Skin disease, Fungal, Student